Overview of Students’ Knowledge Levels Regarding Adolescent Reproductive Health at Senior High School 1 Tasikmalaya, Indonesia - Rahmanagara, Azra Dwi Putri; Khasanah, Uswatun; Yusuf, Ade (GHMJ (Global Health Management Journal), 2024)
Background: Adolescence is significantly associated with psychological development accompanied by sexual developments which together make teenagers more prone to risky behavioral problems. Reproductive health education is important as a provision of knowledge for adolescents regarding reproductive anatomy and physiology, the process of fetal development, and various reproductive problems. Aims: To determine students' understanding of adolescent reproductive health at Senior High School 1 Tasikmalaya, Indonesia. Methods: This research method was quantitative research using descriptive observational methods which was conducted in May 2024 at Senior High School 1 Tasikmalaya. The instrument used was questionnaire. The number of samples used based on calculations using the Slovin’s formula was 282 people. This research used stratified random sampling. Results: The finding of this research showed that 97.54% of the students had a high level of knowledge regarding reproductive health. Based on the puberty indicator, 92.61% of them demonstrated a high level of knowledge. In comparison, 67.61% had a high level of knowledge about reproductive organs, while only 2.11% were found to have low knowledge. Based on the reproductive health care indicator, 88.38% of the students possessed a high level of knowledge. On the pregnancy and sexual behavior indicators, 88.73% also demonstrated a high level of knowledge, while 0.71% was classified as having low knowledge. Conclusion: The level of knowledge of the students regarding adolescent reproductive health at Senior High School 1 Tasikmalaya was primarily classified in the high category.   Received: 25 September 2024  |  Reviewed: 19 October 2024  |  Revised: 23 November 2024  |  Accepted: 30 November 2024.